Production of humic acid and humates - Mohd Hanif, Ahmad Husni; Haruna Ahmed, Osmanu; Abd Rahim, Anuar; Musa, Mohamed Hanafi (2010)
Humic acid is produced from compost by first reacting compost with an alkaline agent to obtain a mixture containing humates. Then, liquid fraction of mixture is separated from solid matter and pH of the liquid fraction separated is adjusted between 1 and 2 with acid. The acidified liquid fraction is allowed to stand for humic acid to precipitate out. Finally, the precipitated humic acid is separated from the acidified fraction. K-humate is produced by reacting humic acid with a potassium source in the presence of water. Compost refers to particularly to composted pineapple lesf residues or other composted materials which contain humic acid. On the other hand, the alkaline agent and the potassium source refer particularly to potassium hydroxide (KOH) solution produced from incinerated pineapple leaf residues or other sources of alkali and potassium.